Long non-coding RNAs modulate glutathione metabolism gene expression and tolerance to Pb stress in root tissue of endophyte-infected rice seedling - He-Fei Sun; Xin-Nan Wang; Ya-Nan Li; Lan-Lan Wang; Yue-Ying Li; Lian-Ju Ma; Xue-Mei Li (Ecotoxicology and Environmental Safety)
Endophyte can improve plant resistance to Pb stress, and long non-coding RNAs (lncRNAs) have been proved to play a vital role in response to environmental stress. However, there are few studies on the role of lncRNAs induced by endophyte in host plants under Pb stress. Therefore, we conducted high-throughput sequencing on root tissue of endophyte-infected and -uninfected rice seedlings under Pb stress, and analyzed the target genes of differentially expressed lncRNAs (DElncRNAs). The results showed that endophyte infection significantly increased plant height, above-ground fresh weight and dry weight, but significantly decreased root length and under-ground dry weight after 5 d of treatment. A total of 413 DElncRNAs (167 down-regulated and 246 up-regulated) were screened. Their target differentially expressed mRNAs (DEmRNAs) were significantly enriched in glutathione metabolism, plasma membrane and mineral elements transfer etc. DEmRNAs were most significantly enriched in glutathione metabolism, thereinto detected total glutathione, reduced and oxidized glutathione contents, glutathione S-transferase and glutathione reductase activities were significantly increased after 5 d of treatment. DElncRNAs and DEmRNAs were combined with miRNA database to construct ceRNA network. DEmRNAs in ceRNA network were mainly participated in carbohydrate metabolic process, peroxidase activity and phenylpropanoid biosynthesis. This study will help to understand the molecular mechanism elicited by endophytic infection within rice seedlings under Pb stress from the perspective of lncRNA.